Folding Identity: A Foucauldian Reading of Time and Space in Anber Onar’s In Case - Shajwan N. Fatah; Christoph Pasour (Journal of Philology and Educational Sciences, 2025)
This paper offers a critical reading of four selected artworks: “Redoubt,” “Displacements No. 11,” “Current,” and “Territories No. 15” from the recent exhibition In Case (2025) by the Cypriot artist Anber Onar. The study explores the philosophical implications of Onar’s artistic choices in fabric, color, and medium through close visual and material analysis. Drawing on Michel Foucault’s concept of heterotopias and Maurice Merleau-Ponty’s phenomenology of perception, this essay examines how the artworks engage with themes of time, space, memory, and the construction of identity. Ultimately, it argues that these artworks operate as layered spaces in which personal and collective histories converge-inviting viewers into a phenomenological encounter with “other” spatialities beyond linear or conventional frames.